Social Security Reform in the US: Lessons from Hungary - András Simonovits (Hungarian Academy of Sciences, Institute of Economics, 2006)
The partial privatization of the US Social Security system was clearly the top economic policy priority for the new Bush administration. While many famous economists, publicists and politicians support, others reject the partial privatization of the Social Security system. The international comparisons have been quite infrequent, concentrated on few countries (Chile, Great Britain and Sweden) and left out similar reforms introduced in similar situations, like in Hungary, Poland and other ex-communist countries. In this article I try to make up for this omission and outline the lessons from the Hungarian reform, started in 1998. The conclusion is simple: such a reform is possible but does not solve the problems of social security.
Keywords: H55; J26; 330; Social Security; Pensions; Prefunding of pensions; United States; Hungary; Soziale Sicherheit; Rentenreform; USA; Ungarn